CT in atypical Pott's disease - Cabrera, MNB; Wang, EHM
Atypical Potts disease present a diagnostic problem. The CT scans of 14 cases of atypical Potts disease were studied and the findings compared with those of classical Potts disease. The CT criteria for classical Potts disease were fulfilled by the 14 cases despite their atypical presentations on plain radiographs. These criteria include paravertebral soft tissue mass with calcifications and a thickened irregular rim, and marginal sclerosis around bone destruction. The authors suggests the routine use of CT to help in the diagnosis of atypical Potts disease.
Acta Medica Philippina,1993 29 ( 4 ) pages 169-172
Keywords: Tuberculosis, Spinal -- diagnosis